Stenochironomus zhengi sp. nov. from Dawei Mountain National Park, Yunnan, China (Diptera: Chironomidae) - Lin, Xiao-Long; Yao, Yuan; Yan, Chun-Cai; Liu, Wen-Bin (Zootaxa, 2021)
A new species, Stenochironomus zhengi Lin & Liu sp. nov., is described and illustrated as adult males. An updated key to males of Stenochironomus from China is presented.